A Pedagogical Perspective on the Definite and the Indefinite Article in the Romanian Language. Challenges for Foreign Learners - Ivancu, Ovidiu (Verbum, 2019)
All Romance languages have developed the definite and the indefinite article via the Vulgar Latin (Classical Latin did not use articles), the language of the Roman colonists. According to Joseph H. Greenberg (1978), the definite article predated the indefinite one by approximately two centuries, being developed from demonstratives through a complex process of grammaticalization. Many areas of nowadays` Romania were incorporated into the Roman Empire for about 170 years. After two military campaign, the Roman emperor Trajan conquered Dacia, east of Danube.The Romans imposed their own administration and inforced Latin as lingua franca.The language of the colonists, mixed with the native language and, later on, with various languages spoken by the many migrant populations that followed the Roman retreat resulted in a new language (Romanian), of Latin origins. The Romanian language, attested in the 16th Century, in documents written by foreign travellers, uses four different types of articles. Being a highly inflected language, Romanian changes the form of the articles according to the gender, the number and the case of the noun As compared to the other Romance languages, Romanian uses the definite article enclitically. Thus, the definite article and the noun constitute a single word. The present paper aims at discussing, analysing and providing an overview of the use of definite and indefinite articles. The general norm and its various exceptions are examined from a broader perspective, synchronically and diachronically. The pedagogical perspective is meant to offer a comprehensible synthesis to foreign learners.
Keywords: Romanian language; Latin; definite article; indefinite article; inflexion; linguistics